The Genesis and Development of The Definition of Land Management: A Look Through The Prism of History - E. A. Pozdnyakova (Теоретическая и прикладная юриспруденция)
The subject of the study is doctrinal research and legislative norms that form and consolidate the definition of land management in the period from 1917 to the present. The basis for the study is the low legislative technique of the draft law “On Land Management” being developed today, the lack of re-evaluation of the definition of land management. Since the legal regulation of the institute of land management cannot be effective without a basic concept, it is advisable, using the historical method, to analyze the existing definitions of land management, to determine its stable elements that could be applied when developing a new draft law.